Big five personality factors, emotional intelligence and job satisfaction among academic staff of public research universities in Klang Valley, Malaysia - Mehrad, Aida (2015)
The purpose of the present study is to determine the relationship between big five personality factors, emotional intelligence, and job satisfaction. It also examines the mediation effect of emotional intelligence on the relationship between big five personality factors and job satisfaction. The study involved 440 academic staff (236 female and 204 male) from public research universities in Klang Valley, Malaysia. Job satisfaction is important issue in educational system which neglect to it causes various problems at university. Thus, more studies are required to determine the effective factors on job satisfaction. This study applied correlational analysis and cross-sectional design. Respondents were selected by multi-stage sampling and data collection conducted among academic staff at Universiti Putra Malaysia (UPM), Universiti Kebangsaan Malaysia (UKM), and University of Malaya (UM). Big five personality factors (neuroticism, extraversion, openness, agreeableness, and conscientiousness) as independent variables were measured by Big Five Inventory (BFI). Besides that, the emotional intelligence (perception of emotion, utilization of emotion, managing own emotions, and managing others’ emotions) as mediator variables were evaluated by Schutte Self- Report Emotional Intelligence Test (SSEIT), whereas the job satisfaction as a dependent variable was assessed by Job Descriptive Index (JDI). The statistical techniques applied in the study were descriptive statistics, independent sample t-test, Analysis of Variance (ANOVA), Pearson correlation coefficient, multiple linear regression analysis, and mediation analysis (Sobel test). This study used three theoretical approaches and models (Herzberg’s Motivation-Hygiene Theory, Five-Factor Model, and Mayer and Salovey Model). The study found that there are differences in job satisfaction based on receive reward, status of designation, age, income, level of education, and years of employment. The findings also indicated a positive correlation among perception of emotion, utilization of emotion, managing own emotions, managing others’ emotions, conscientiousness, agreeableness, and openness with job satisfaction. On the other hand, there is a negative correlation between neuroticism and job satisfaction, whereas no correlation is observed between extraversion and job satisfaction. Big five personality factors also showed a significant relationship with almost all emotional intelligence factors except utilization of emotion and neuroticism. This study proved that the utilization of emotion and neuroticism allow to predict the level of job satisfaction. These two factors collectively, accounted for 7% of variance in job satisfaction. Among the factors of emotional intelligence, only the utilization of emotion plays the role as a mediator of the relationship of openness, agreeableness, and conscientiousness with job satisfaction. Based on the findings of this study it can be concluded that job satisfaction is influenced by socio-demographic factors, big five personality factors, and emotional intelligence. The academic staff who receive reward, possess a doctoral degree, and permanent designation show high level of job satisfaction. In addition, job satisfaction varies according to age, income, and years of employment. The conscientiousness, the openness, and the agreeableness of the academic staff show better reaction toward difficulties at the workplace although the neurotic illustrate uncommon organizational behavior at university. Other than that, the academic staff who use their emotional intelligence have better feeling toward their job and university. They have more emotional intelligence compared to the neurotic. The academic staff who achieved high scores in utilization of emotion have a higher level of job satisfaction compared to those who obtained high scores in neuroticism. Likewise, those who apply the utilization of emotion get a better job satisfaction. The study proposes several recommendations for ministry of higher education (MOHE), universities, managers, and academic staff to improve the level of job satisfaction by considering basic human needs, and distinguishing the effective personality factors and emotions. This study also suggests that the university should acquire the early information on the new staff’s personality by using the suitable screening test as prevention and to plan the treatment strategy to the staff with neurotic personality. The university must specifically consider the emotional intelligence in any treatment and prevention program to increase the level of job satisfaction among staff. To sum up, the study shed new light in the context of social psychology especially in job satisfaction context among academic staff at Malaysian public research universities.